A Comparison of Precipitation Measurements with a PWS100 Laser Sensor and a Geonor T-200B Precipitation Gauge at a Nival Glacial Zone in Eastern Tianshan, Central Asia - Yufeng Jia; Zhongqin Li; Chunhai Xu; Shuang Jin; Haijun Deng (Atmosphere, 2020)
Precipitation is a key process in the hydrologic cycle. However, accurate precipitation data are scarce in high mountainous areas, mainly restricted by complex topography, solid precipitation and sparse recording stations. In order to evaluate the quality of precipitation measurement, this study conducted a comparison campaign of precipitation measurements with the PWS100 laser sensor and the Geonor T-200B rain gauge for an entire year from 30 April 2018 to 1 May 2019 at an elevation of 3835 m in a nival glacial zone in eastern Tianshan, Central Asia. The results show that the daily precipitation values recorded by Geonor T-200B and PWS100 are well correlated and the annual precipitation amounts recorded by the two instruments differ by 7%, indicating good capabilities of both instruments in solid precipitation measurement. However, the amount of precipitation measured by Geonor T-200B was 36 mm lower in June to August and 120 mm higher in the remaining months compared with the values measured by PWS100. Our study indicated that Geonor T-200B is more efficient than PWS100 in terms of catching solid precipitation measurements. According to the PWS100 data, the experiment site was dominated by solid precipitation particles, accounting for 60% of total precipitation particles. Based on the precipitation particle and in-situ air temperature measurements, a set of temperature thresholds were established to discriminate rain, sleet and snow. The threshold temperature of rainfall and snowfall is −1.5 and 8 °C, respectively. When air temperature ranges from −1.5 to 8 °C, sleet occurs, meanwhile the ratio of rain to snow depends on air temperature.